MRI-guided focused ultrasound thalamotomy in non-ET tremor syndromes. (22nd August 2017) - Fasano, Alfonso; Llinas, Maheleth; Munhoz, Renato P.; Hlasny, Eugen; Kucharczyk, Walter; Lozano, Andres M.
Abstract : Objective: To report the 6-month single-blinded results of unilateral thalamotomy with MRI-guided focused ultrasound (MRgFUS) in patients with tremors other than essential tremor. Methods: Three patients with tremor due to Parkinson disease, 2 with dystonic tremor in the context of cervicobrachial dystonia and writer's cramp, and 1 with dystonia gene–associated tremor underwent MRgFUS targeting the ventro-intermedius nucleus (Vim) of the dominant hemisphere. The primary endpoint was the reduction of lateralized items of the Tremor Rating Scale of contralateral hemibody assessed by a blinded rater. Results: All patients achieved a statistically significant, immediate, and sustained improvement of the contralateral tremor score by 42.2%, 52.0%, 55.9%, and 52.9% at 1 week and 1, 3, and 6 months after the procedure, respectively. All patients experienced transient side effects and 2 patients experienced persistent side effects at the time of last evaluation: hemitongue numbness and hemiparesis with hemihypoesthesia. Conclusions: Vim MRgFUS is a promising, incision-free, but nevertheless invasive technique to effectively treat tremors other than essential tremor. Future studies on larger samples and longer follow-up will further define its effectiveness and safety. Clinicaltrials.gov identifier: NCT02252380. Classification of evidence: This study provides Class IV evidence that for patients with tremor not caused by essential tremor, MRgFUS of the Vim improves the tremor of the contralateral hemibody at 6 months.